Was the Maternal Health Cash Transfer Programme in Nigeria Sustainable and Cost-Effective? - Onwujekwe, Obinna; Ensor, Tim; Ogbozor, Pamela; Okeke, Chinyere; Ezenwaka, Uche; Hicks, Joseph P.; Etiaba, Enyi; Uzochukwu, Benjamin; Ebenso, Bassey; Mirzoev, Tolib (Frontiers in Public Health, 2020)
Background: The Subsidy Reinvestment and Empowerment Programme (SURE-P), Maternal and Child Health (MCH) was introduced by the Nigerian government to increase the use of skilled maternal health services and reduce maternal mortality. The programme, funded out of a reduction in the fuel subsidy, was implemented between October 2012 and April 2015 and incorporated a conditional cash transfer to women to encourage use of facility based maternal services. We seek to assess the incremental cost effectiveness and long term impact of the conditional cash transfer element of the programme. Methods: An impact analysis and incremental cost-effectiveness analysis of conditional cash transfers (CCTs) is undertaken taking a health service perspective toward costs of the intervention. The study was undertaken in Anambra state, comparing areas that received only the investment in health services with areas that implemented the conditional cash transfer programme. An interrupted time series analysis of the programme outputs was undertaken. These were combined with a programme costing to determine the incremental cost per output. Findings: Maternal services provided to patients in conditional cash transfer areas accelerated rapidly from the middle of 2014 until after the programme in late 2015. The costs of providing services in each Primary Health Center facility was US $52,128 in the areas that only invested in health services compared to US $90,702 in facilities that also provided cash transfers. Much of the additional cost was in managing cash transfers. The incremental cost in the cash transfer areas was $572 for delivery care and $11 for antenatal care. If the programme was to be integrated as a regular service in the public health system, the cost of a delivery is estimated to fall to $389 and to $188 if 2015 levels of activity are assumed. Conclusion: Although the cost of CCTs as originally constituted as a vertical programme are relatively high compared to other similar programmes, these would fall substantially if integrated into the main health system. There is also evidence of sustained impact beyond the end of the funding suggesting that short term programmes can lead to a long-term change in patterns of health seeking behavior.